Early Christians Adapting to the Roman Empire : Mutual Recognition - Huttunen, Niko, (Novum Testamentum, Supplements ;, 2020)
In Early Christians Adapting to the Roman Empire: Mutual Recognition Niko Huttunen challenges the interpretation of early Christian texts as anti-imperial documents. He presents examples of the positive relationship between early Christians and the Roman society. With the concept of "recognition" Huttunen describes a situation in which the parties can come to terms with each other without full agreement. Huttunen provides examples of non-Christian philosophers recognizing early Christians. He claims that recognition was a response to Christians who presented themselves as philosophers. Huttunen reads Romans 13 as a part of the ancient tradition of the law of the stronger. His pioneering study on early Christian soldiers uncovers the practical dimension of recognizing the empire.